A randomized, placebo-controlled phase III trial of masitinib plus gemcitabine in the treatment of advanced pancreatic cancer - Deplanque, G; Demarchi, M; Hebbar, M; Flynn, P; Melichar, B; Atkins, J; Nowara, E; Moyé, L; Piquemal, D; Ritter, D; Dubreuil, P; Mansfield, C D; et al. (Annals of oncology, 2015)
BACKGROUND: Masitinib is a selective oral tyrosine-kinase inhibitor. The efficacy and safety of masitinib combined with gemcitabine was compared against single-agent gemcitabine in patients with advanced pancreatic ductal adenocarcinoma (PDAC). PATIENTS AND METHODS: Patients with inoperable, chemotherapy-naïve, PDAC were randomized (1 : 1) to receive gemcitabine (1000 mg/m(2)) in combination with either masitinib (9 mg/kg/day) or a placebo. The primary endpoint was overall survival (OS) in the modified intent-to-treat population. Secondary OS analyses aimed to characterize subgroups with poor survival while receiving single-agent gemcitabine with subsequent evaluation of masitinib therapeutic benefit. These prospectively declared subgroups were based on pharmacogenomic data or a baseline characteristic. RESULTS: Three hundred and fifty-three patients were randomly assigned to receive either masitinib plus gemcitabine (N = 175) or placebo plus gemcitabine (N = 178). Median OS was similar between treatment-arms for the overall population, at respectively, 7.7 and 7.1 months, with a hazard ratio (HR) of 0.89 (95% CI [0.70; 1.13]. Secondary analyses identified two subgroups having a significantly poor survival rate when receiving single-agent gemcitabine; one defined by an overexpression of acyl-CoA oxidase-1 (ACOX1) in blood, and another via a baseline pain intensity threshold (VAS > 20 mm). These subgroups represent a critical unmet medical need as evidenced from median OS of 5.5 months in patients receiving single-agent gemcitabine, and comprise an estimated 63% of patients. A significant treatment effect was observed in these subgroups for masitinib with median OS of 11.7 months in the 'ACOX1' subgroup [HR = 0.23 (0.10; 0.51), P = 0.001], and 8.0 months in the 'pain' subgroup [HR = 0.62 (0.43; 0.89), P = 0.012]. Despite an increased toxicity of the combination as compared with single-agent gemcitabine, side-effects remained manageable. CONCLUSIONS: The present data warrant initiation of a confirmatory study that may support the use of masitinib plus gemcitabine for treatment of PDAC patients with overexpression of ACOX1 or baseline pain (VAS > 20mm). Masitinib's effect in these subgroups is also supported by biological plausibility and evidence of internal clinical validation. TRIAL REGISTRATION: ClinicalTrials.gov:NCT00789633.
Keywords: duktální karcinom slinivky břišní; Carcinoma, Pancreatic Ductal; deoxycytidin; proporcionální rizikové modely; Spojené státy americké; nádory slinivky břišní; Humans; tyrosine–kinase inhibitor; Pharmacogenetics; inhibitory proteinkinas; Antimetabolites, Antineoplastic; lidé středního věku; Proportional Hazards Models; Benzamides; Precision Medicine; analýza podle původního léčebného záměru; Predictive Value of Tests; Biomarkers, Tumor; Female; rizikové faktory; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; pancreatic cancer; farmakogenetika; výsledek terapie; senioři; lidé; individualizovaná medicína; Europe; Gemcitabine; United States; Pyridines; PDAC; pain; genetic biomarker; časové faktory; Piperidines; gemcitabin; nádorové biomarkery; oxidoreduktasy; Adult; Protein Kinase Inhibitors; thiazoly; ženské pohlaví; Male; Pancreatic Neoplasms; Middle Aged; prediktivní hodnota testů; Deoxycytidine; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; protinádorové antimetabolity; Aged, 80 and over; pyridiny; Intention to Treat Analysis; benzamidy; senioři nad 80 let; Thiazoles; piperidiny; ACOX1; mužské pohlaví; prospektivní studie; Oxidoreductases; Time Factors; Evropa; Risk Factors; Prospective Studies